Modification of fliposomes with a polycation can enhance the control of pH-induced release - Lokova AY (Dove Medical Press, 2019)
Anastasia Yu Lokova, Olga V Zaborova Department of Chemistry, M.V. Lomonosov Moscow State University, 119991 Moscow, Russian Federation Purpose: Nowadays, the development of stimuli-sensitive nanocontainers for targeted drug delivery is of great value. Encapsulation of a drug in a pH-sensitive liposomal container not only provides protective and transport functions, but also helps to create a system with a controlled release mechanism.Methods: In this study, we investigated the influence of a cationic polypeptide on the pH-induced release of anticancer drug doxorubicin (DXR) from the anionic fliposomes – liposomes consisting of a neutral lipid, an anionic lipid (prone to interact with a polycation), and a lipid trigger (imparting the pH-sensitivity).Results: First, we showed the possibility to control the pH-induced release by the simple modification of the anionic fliposomes with linear polylysine. Second, we optimized the fliposomal composition such that the obtained fliposomes responded to the pH changes only when complexed with the polycation (“turning on” the release). Finally, pH-induced release from the polylysine-modified anionic fliposomes was tested on an anticancer drug DXR.Conclusion: We have succeeded in developing “smart” stimuli-sensitive nanocontainers capable of tunable controlled release of a drug. Moreover, based on the data on release of a low molecular salt, one can predict the release profile of DXR. Keywords: polylysine, polymer–colloid complex, stimuli-sensitive nanocontainer, pH-sensitivity, controllable drug release